FORECASTING HIGH WAVES IN THE COASTAL WATERS OF CLUNGUP AS A SUPPORT FOR THE RESILIENCE OF COASTAL ECOSYSTEMS - Isdianto, Andik (Journal of Environmental Engineering and Sustainable Technology, 2021)
Coastal ecosystems are very vulnerable to environmental changes, and one of the variables of resilience in coastal areas is wave height. Clungup Beach is one of the beaches located in South Java with the characteristics of high waves. Analysis of wave height forecasting to minimize environmental damage in the future. The wave height forecasting method is carried out by two methods, namely Fisher Tippet-1 and Weibull, with the aim of comparing the results of forecasting the resulting waves and validating the forecast data. The source of wave data for 10 years (2009 - 2018) was obtained from the ECMWF (European Center for Medium-Range Weather Forecasts) website. The results of data analysis show that the wave height of Clungup Beach for a period of 10 years (2009 - 2018) with the highest value in July 2013, namely 2.67 m and the lowest in June 2010 with a value of 2.28 m, which is classified as a wave extreme in accordance with the Regulation of the Head of BMKG No. KEP. 009 of 2010. Wave forecasting with the Fisher Tippet-1 method return period in 2020 is 2.48 m and in the next 50 years (2069) is 2.76 m. Whereas in the Weibull method, the wave value for 2020 is 2.43 m and for the next 50 years (2069) is 3.01 m. The two methods used have the equation that the wave height that will occur in the Clungup Beach area will experience an increase (upward trend). This will be the basis for determining the scenario of coastal area protection, so that the resilience of coastal ecosystems will be well realized.